Growth Evaluation of Backcross Progenies BC2F1 Experiencing Submergence and Non-submergence at BC1F1 and its Parents - Jati, Winggi Anggun; Agus Suwignyo, Rujito; Susilawati; Muhardiyanto, Cahya (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
The utilization of dual-resistant varieties that are resistant to soaking and drought in certain periods is an alternative to rice cultivation in swampy land. Inpara 8 is a variety that is confirmed to have SUB 1 gene, resistant to submerged stress and Inpago 5 is identified to be resistant to drought stress. Crosses were made between Inpara 8 (donor parent) with Inpago 5 (recipient parent), resulting in F1, then F1 was crossed back with Inpago 5 and produced BC1F1, then crossed back with Inpago 5 to become BC2F1. This paper contains an evaluation of the growth of BC2F1, which in the BC1F1 stage experienced submerged stress in the vegetative phase and which did not experience submerged stress. The research was carried out in August 2021 - January 2022 at the Greenhouse of the Department of Agricultural Cultivation, Faculty of Agriculture, Sriwijaya University. The results showed that in the vegetative phase, progeny BC2F1 TR has an average value of the highest per plant (113.64 cm) and the average per plant height Inpara 8 (3.93). In the generative phase, the fastest flowering time on the accession of BC2F1 TR (68 days), the fastest harvest time on Inpara 8 (122.93 days), while for the amount of grain per panicle, the amount of grain per clump, and dry weight on Inpago 5 (529.60 g, 2648 g, and 11.62 g). The average yield of BC2F1 progeny is more similar to Inpago 5 as the recipient parent. Both progeny have the same Sub 1 gene in them and can survive to produce, but Accessions that have experienced previous submerged stress are more vulnerable to growth so they have an impact on the resulting production.